Efficacy of Primary Percutaneous Coronary Intervention (PCI) Performed Through a Transradial Approach in Patients with ST- Segment Elevation Myocardial Infarction (STEMI) at a Tertiary Care Cardiac Center - Badr Mansoor, Osama, Muhammad Iqbal, Asim Ali, Farrukh Malik, Abdul Wahab Buzdar, Asadullah, Rahid Ullah, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective of Study: The study aimed to evaluate the clinical outcomes, safety, and efficacy of primary percutaneous coronary intervention (PCI) performed through a transradial approach in patients with ST- Segment elevation myocardial infarction (STEMI) at a tertiary care cardiac center. Place of Study: The study was conducted at the National Institute of Cardiovascular Diseases, Karachi, Pakistan Duration of Study: The study was conducted over a period of six months, from April, 2022 to September, 2022. Methods: A total of 250 consecutive patients who underwent primary PCI through a transradial approach were included in the study. Demographic, clinical, procedural, and angiographic data were collected. The primary outcome measure was the incidence of major adverse cardiovascular events (MACE), including death, myocardial infarction, target vessel revascularization, and stroke at 30 days and six months' post-procedure. Secondary outcomes included procedural success, access site complications, and door-to-balloon time. Results: The mean age of participants was 58.7 ± 10.2 years, with 72.8% being male. The procedural success rate was 96.4%. The incidence of MACE at 30 days and six months was 5.6% and 8.8%, respectively. Access site complications were observed in 2.8% of patients, and the mean door-to-balloon time was 81.3 ± 25.6 minutes. Multivariate analysis identified diabetes mellitus and triple-vessel disease as independent predictors of MACE. Conclusion: Primary PCI through a transradial approach at a tertiary care cardiac center in Karachi, Pakistan, demonstrated high procedural success rates, favorable clinical outcomes, and a low incidence of access site complications. This approach may be considered a safe and effective treatment option for patients with acute coronary syndromes. Keywords: primary percutaneous coronary intervention, transradial approach, ST- segment elevation myocardial infarction, major adverse cardiovascular events, tertiary care cardiac center, access site complications, door-to-balloon time